Molecular Detection of Rust Fungus (Puccinia spp.) on Sugarcane using ITS region - Tanzil, Ahmad Ilham; Maulida, Dinda Mala; Fanata, Wahyu Indra Duwi; Neliana, Intan Ria; Sugiharto, Bambang; Magnon, Cassidy (Universitas Negeri Semarang, 2025)
Identifying pathogenic fungi at the species level based on morphology, especially for leaf rust, is quite difficult. Further investigation, such as molecular techniques, is required to identify leaf rust fungi precisely. One way that can be employed is DNA barcoding. This study seeks to detect leaf rust fungi (Puccinia spp.) on sugarcane. Accurate species identification allows early detection of Puccinia kuehnii, helping farmers and extension agencies to apply targeted control strategies. A fungal sample was collected from sugarcane fields in Bondowoso, East Java, Indonesia. Morphological identification was done with an SEM, whereas molecular identification was done through DNA extraction, amplification, visualization, sequencing, and phylogenetic tree creation. The primers employed are obtained from the ITS region of ribosomal DNA, which contains enough diversity to differentiate fungi at the species level. The amplification findings revealed a DNA band of 500 bp at both loci. Sequencing results indicate that samples The sequencing results indicatethat the samples from Bondowoso are closely related to the Puccinia kuehnii sequence from NCBI. The findings of the phylogenetic tree construction revealed that samples from both locations are still associated with P. kuehnii sequences from other nations. This is the first study documenting P. kuehnii in Indonesia, especially East Java, that integrates morphological and molecular characterization.